The Dynamics of Islamophobia after the September 11 Tragedy in the United States Society on Terrorism - Yuwono, Ardi Tri; Sebastian, Andi; Ngasiman, Nur'irfaan Adrus bin; Ahad, Eizzah Bukhari binti; Wiratama, Nara Setya; Budianto, Agus (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
Nationalism can be seen as a double-edged sword, which functions as a binding of a nation's identity but can also trigger Islamophobia and terrorism. After the September 11, 2001 attacks in the United States, the country began accusing various groups and countries of being involved in acts of terrorism through Islamophobia by promoting its nationalist spirit. This research aims to explore the side of nationalism that can contribute to the rise of Islamophobia and terrorism in the United States. The methods used in this study are historical methods and radical hermeneutics with a qualitative approach. The September 11, 2001, attacks in the United States indicate the existence of four stages that affect the development of Islamophobia and terrorism in the United States, namely: Events that create deep fear and trauma in American society, agents and mass media who began to spread fear excessively, so that the American people increasingly felt threatened and sought protection, the emergence of a figure who is considered a savior by the people of the United States, who then instigates other groups with the spirit of nationalism so that there is a division in the society of the United States; and the incited people of the United States began to demand revenge against a person or group, namely Muslims.